2019
DOI: 10.1049/iet-ipr.2019.0532
|View full text |Cite
|
Sign up to set email alerts
|

Trilateral convolutional neural network for 3D shape reconstruction of objects from a single depth view

Abstract: In this study, the authors propose a novel three‐dimensional (3D) convolutional neural network for shape reconstruction via a trilateral convolutional neural network (Tri‐CNN) from a single depth view. The proposed approach produces a 3D voxel representation of an object, derived from a partial object surface in a single depth image. The proposed Tri‐CNN combines three dilated convolutions in 3D to expand the convolutional receptive field more efficiently to learn shape reconstructions. To evaluate the propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Meanwhile, the discriminator was dedicated to classifying real data and fake data. Based on the targets of the G and D modules, the objective function was set as Equation (3). The optimization criteria are to minimize the loss in training the generator and maximize the loss in training the discriminator.…”
Section: Training Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the discriminator was dedicated to classifying real data and fake data. Based on the targets of the G and D modules, the objective function was set as Equation (3). The optimization criteria are to minimize the loss in training the generator and maximize the loss in training the discriminator.…”
Section: Training Detailsmentioning
confidence: 99%
“…Nowadays, 3D representation of real-world objects has become a core concept for vision, robotics, augmented reality and virtual reality applications, for its powerful geometric representation ability [1]. In computer vision and graphics, 3D object modelling can take on various forms of representation [2][3][4]. Hitherto, most researchers choose the 3D voxel grids or a collection of images to represent 3D object.…”
Section: Introductionmentioning
confidence: 99%
“…The distance of each slide is called the convolution step [15]. In the process of convolution operation, for the input image and convolution kernel with a certain size, the number of feature extraction is determined by the step size, and the smaller the step size, the more times the feature is extracted [16].…”
Section: Cnn Structurementioning
confidence: 99%
“…Additionally it was shown that by adopting Bernstein Basis Function Networks (BBFNs) it is also possible to solve the task of reconstructing a 3D shape [27]. A trilateral convolutional neural network (Tri-CNN) that uses three dilated convolutions in 3D to extend the convolutional receptive field was applied on the ShapeNet and Big Data for Grasp Planning [28] data sets to obtain 3D reconstruction from a single depth image [29].…”
Section: Introductionmentioning
confidence: 99%